Effect of Cuminum cyminum and Rhus pentaphylla extracts on status epilepticus induced by intrahippocampal injection of kainic acid in rat (Bangladesh Journal of Pharmacology, 2023)
This study aims to evaluate the anticonvulsant effect of the aqueous extract of Rhus pentaphylla and Cuminum cyminum (300 mg/kg), orally, 45 min before intrahippocampal injection of kainic acid (1 µg/µL). The scoring of seizure severity, latency of seizures and duration of total seizures were recorded in 90 min. Both extracts showed the presence of polyphenols, flavonoids, alkaloids and tannins compounds. These extracts exhibited potent antioxidant activity and showed an attenuation of severe convulsive seizures, a significant decrease in the frequency and duration of seizures and prolonged the latency of the onset seizure (p